Growth and yield of barley in relation to grasshopper feeding damage - Begna, Sultan H.; Fielding, Dennis J. (Canadian Journal of Plant Science, 2008)
Grasshoppers are common pests of barley (Hordeum vulgare L.) in subarctic Alaska and cause substantial crop loss during outbreaks, but there is little information about the growth response of barley to grasshopper feeding damage. In two growth chamber experiments, we studied the effect of four densities (0, 1, 2, and 3 pot -1 , equivalent to 0, 25, 50 and 75 grasshoppers m -2 ) of grasshoppers (Melanoplus sanguinipes F.) on the above-and below-ground growth of barley (eight plants per pot). Plants were exposed to grasshoppers beginning in the 3rd to 4th leaf stage (exp. 1) and in 1st to 2nd leaf stage (exp. 2). Plants were harvested and growth variables were measured shortly after anthesis and at maturity. Generally, the reduction in above-ground dry matter, at the highest density was 29 and 47% for exp. 1 and exp. 2, respectively. Effects of grasshoppers on below-ground growth (dry matter and surface area of roots) was less consistent than on above-ground variables; however, at the highest grasshopper density in exp. 2, dry matter and surface area of roots were reduced by about 40–53%.Grain yield (pooled over experiments) decreased by 19 and 36% for grasshopper densities of 2 and 3 pot -1 , respectively. Most of the yield loss was accounted for by reduced seed weights, while protein content per seed remained nearly constant. The proportion of total above-ground dry matter represented in harvested grain and root:shoot ratios were not affected by grasshopper feeding. These results provide greater understanding of plant responses to insect feeding damage and will lead to more accurate estimates of economic injury levels. Key words: Cropyield loss, economic injury level, harvest index, Insecta